2010
DOI: 10.1016/j.pmrj.2010.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Transversus Abdominis Thickness With Use of the Abdominal Drawing‐In Maneuver During a Functional Task

Abstract: Subjects in this study demonstrated the ability to voluntarily activate the TrA during upright static and functional tasks. Additionally, the TrA thickness may change in a direction-specific manner. These findings support a protective role of the ADIM during functional activity and may add information to ways for promoting low back pain prevention. Future studies should include the effectiveness in the use of ADIM during functional tasks for the prevention of low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 44 publications
(93 reference statements)
5
54
2
Order By: Relevance
“…The ADIM has been found to increase muscle thickness during a standing task and may provide additional stabilization. 27 We are unable to conclude if multiple training sessions or voluntary activation of the abdominal muscles would provide additional support to the lumbar spine. Ultrasound imaging was using in the current study to measure muscle thickness, and while ultrasound has been found to be correlated with electromyographic activity, 24 ultrasound imaging is only able to observe muscle activation through thickness changes and may not provide information about the onset or timing of muscle activation.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The ADIM has been found to increase muscle thickness during a standing task and may provide additional stabilization. 27 We are unable to conclude if multiple training sessions or voluntary activation of the abdominal muscles would provide additional support to the lumbar spine. Ultrasound imaging was using in the current study to measure muscle thickness, and while ultrasound has been found to be correlated with electromyographic activity, 24 ultrasound imaging is only able to observe muscle activation through thickness changes and may not provide information about the onset or timing of muscle activation.…”
Section: Discussionmentioning
confidence: 88%
“…Standing measures of muscle function of abdominal-muscle thickness in gravity-loaded positions have been observed to be both reproducible 33 and reliable. 26,27,32,33 Since the PAR is a ratio of the TrA thickness in comparison with the entire lateral wall between contracted and resting states, any increase in PAR could indicate an increased ability to activate the TrA independently from the other abdominal muscles. The current findings indicate that individuals with a history of LBP can increase TrA PAR in a standing position after a single bout of exercise, and the addition of biofeedback may have a greater effect on TrA PAR (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations